Rotifera from the Mediterranean Sea, with description of ten new species - Smet, Willem H. De Smet (Zootaxa, 2015)
A total of 43 rotifer taxa, belonging to 14 genera, was identified in 47 psammon and periphyton samples collected in the northern part of the western basin of the Mediterranean Sea. Of these, 10 previously described species are new to the Mediterranean, 10 species are new to science and could be described, and 5 others are potential new ones of which insufficient material was available to warrant a full description. Rotifers formed a constant component of meiofauna, from the eulittoral to at least 8 km off shore and a depth of 66 m. A clear zonation was apparent with one to two species only found in the eulittoral zone and sublittoral fringe, and 42 taxa occurring in the sublittoral zone. The trophi of seven previously known species are redescribed based on scanning electron microscopy. Dicranophorus bulgaricus Althaus, 1957 is redirected to Allodicranophorus gen. nov. and Lepadella pontica Althaus, 1957 to Halolepadella gen. nov.